First‐Row Transition Metal Based Catalysts for the Oxygen Evolution Reaction under Alkaline Conditions: Basic Principles and Recent Advances. Issue 45 (28th September 2017) - Lu, Fei; Zhou, Min; Zhou, Yuxue; Zeng, Xianghua
Abstract: Owing to its abundance, high gravimetric energy density, and environmental friendliness, hydrogen is a promising renewable energy to replace fossil fuels. One of the most prominent routes toward hydrogen acquisition is water splitting, which is currently bottlenecked by the sluggish kinetics of oxygen evolution reaction (OER). Numerous of electrocatalysts have been developed in the past decades to accelerate the OER process. Up to now, the first‐row transition metal based compounds are in pole position under alkaline conditions, which have become subjects of extensive studies. Recently, significant advances in providing compelling catalytic performance as well as exploring their catalytic mechanisms have been achieved in this area. In this review, we summarized the fundamentals and recent progresses in first‐row transition metal based OER catalysts, with special emphasis on the pathways of promoting catalytic performance by concrete strategies. New insight into material design, particularly the role of experimental approaches in the electrocatalytic performance and reaction mechanisms of OER are expected to be provided. Abstract : The optimization of first‐row transition metal based catalysts for the oxygen evolution reaction is considerably important to accelerate water splitting. Basic principles and emerging optimization strategies are categorized in terms of Gibbs free energy tuning, modification of electron transport, and enlargement of surface area, with particular emphasis on promoting catalytic performance by concrete approaches.